Hubungan Penerapan Oral Hygiene dan Posisi Semifowler Dengan Kejadian Ventilator Associated Pneumonia (VAP) Pada Pasien Terintubasi di Ruang ICU RSUD Khidmat Sehat Afiat Tahun 2025 - Jamaludin; Daeli, Weslei (PT. Alahyan Publisher Sukabumi, 2026)
VAP prevention efforts need to be optimally implemented through evidence-based nursing interventions, including oral hygiene and the semi-Fowler's position. This study aims to determine the relationship between oral hygiene and the semi-Fowler's position and the incidence of Ventilator-Associated Pneumonia (VAP) in intubated patients in the ICU of Khidmat Sehat Afiat Regional Hospital in 2025. This study used a quantitative research design with an observational analytical approach. The population was all intubated patients treated in the ICU of Khidmat Sehat Afiat Regional Hospital, with the sample determined based on inclusion and exclusion criteria. Data were collected using observation sheets to assess oral hygiene practices, the semi-Fowler's position, and the incidence of VAP based on clinical indicators and supporting examinations. Data were analyzed using univariate and bivariate methods to determine the relationship between the independent and dependent variables. The results are expected to demonstrate a significant association between oral hygiene practices and the semi-Fowler's position and the incidence of VAP in intubated patients. This research is expected to serve as a basis for strengthening critical care nursing practices, particularly in the development and implementation of standard operating procedures for VAP prevention in the ICU, as well as improving the safety and quality of nursing care for critically ill patients.